Outdoor recreation of whites in the Cape Town metropolitan area : the resource base and utilization patterns - Taylor, V.(Vincent) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1984.